Portal venous gas after a failed endoscopic retrograde cholangiopancreatography attempt in a patient with a large hepatocellular carcinoma: A case report. Issue 3 (9th January 2021) - Cassese, Gianluca; Maione, Francesco; Alagia, Mariantonietta; Ambrosio, Luisa; Caruso, Emanuele; Chini, Alessia; Cimmino, Claudio; Nasto, Riccardo Aurelio; Pegoraro, Francesca; Giglio, Mariano Cesare; De Palma, Giovanni Domenico
Abstract: The cause of hepatic portal vein gas (HPVG) is variable. Good knowledge of the possible causes, combined with the clinical assessment of the patient and a good quality imaging, is required to correctly identify the underlying cause of HPVG and to best predict the prognosis. Abstract : The cause of hepatic portal vein gas (HPVG) is variable. Good knowledge of the possible causes, combined with the clinical assessment of the patient and a good quality imaging, is required to correctly identify the underlying cause of HPVG and to best predict the prognosis.